Entrepreneurial behavior measurement of students in one Ecuadorian university and one Colombian, according to their relationship with business thinking (Business Vision, 2022)
The objective of this study was to measure entrepreneurship behaviors of the students from Universidad Politécnica Estatal del Carchi in Ecuador and the Universidad de San Buenaventura in Cali, Colombia, and their relationship with business thinking. The methodological procedures, which proved McClelland’s theory, were carried out with a large sample of university students (801 in Ecuador and 564 in Colombia). The collection of data for both universities was made online by a questionnaire of 50 questions plus 5 of correction, which use a Likert scale, during March of 2021. The SPSS software and the method of extraction of factors with maximum verisimilitude and rotation Promax were used to analyze the measure model, as well as the configurable invariance and metrics, as the previous step for the development of a model of structural equations (SEM). The measure model exercise, firstly verify the reliability and validity of model and then validate the configurable invariance and metrics per-country. In a future delivery, a SEM analysis will be made. There are behaviors that are patterns of a successful seller: persistence, opportunities finder, persuasion, and self-confidence. Furthermore, using the curriculum developed in UPEC, mentioned behaviors are pretended to be reached whose objective is to increase the entrepreneurial intention with propensity to close sales. In the same way, behaviors related with a successful manager were also found. For example, calculated risk-taking, fulfilment, systematic planning, and information search that can be intervened so that the entrepreneur increases its intention to create companies.
Keywords: Entrepreneurial behaviors; business skills; entrepreneurial chair; exploratory factor analysis; confirmatory factor analysis; configural and metric invariance